LA MAGIE IMITATIVE. RITUELS OBSCURS, RITUELS AMOUREUX [THE IMITATIVE MAGIC. DARK RITUALS, LOVE RITUALS] - Baros, Linda Maria (Cinematographic Art Documentation, 2012)
Vasile Voiculescu’s short story The Taimen presents obscure rituals which intermingle imitative magic and demonomagic in order to bind, through an erotic ligatura, a fisherman to a succubus embodied in a bewitched ichthyologic creature. In exchange of his faith in God, the fisherman is given the capacity to transform the diabolic taimen in a charming woman. On one hand, this anthropomorphism can be conceived as the result of the young man’s emotional tendencies. By means of magic – which puts his erotic desire into action –, he materializes his own psychic processes. On the other hand, it can be considered as a misleading work of the Devil, who is thus able to seize the fisherman’s ignited heart.
https://katalog.adlr.link/Record/ai-53-173486